OTOTOXICITY OF STREPTOMYCIN AND GENTAMICIN IN IRAQI RAMS - J. AL-Saffar, F.; J. Balash, K.; K. AL-Shaikhly , A. (The Iraqi Journal of Veterinary Medicine, 1992)
The aim of this research was to investigate the ototoxic effects of two different aminoglycoside antibiotics, namely streptomycin and gentamicin on Iraqi rams. These antibiotics were injected intramuscularly using the therapeutic and double doses of each. The data showed no clear differences in their effects on both vestibular and cochlear structures of inner ear as they showed similar histological changes but in different intensities.